Infusing Islamic financial literacy in mathematics education for Islamic school - Kusumawati, Intan Bigita; Fachrudin, Achmad Dhany; Putri, Ratu Ilma Indra; Zulkardi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Knowledge of financial literacy, including Islamic financial literacy which has been widely used in various financial products, intersects with several domain areas in mathematical concepts, especially in basic arithmetic which requires students to perform basic calculations before making the right financial decisions. This research aims to develop an instructional design of social arithmetic learning using Math-based Islamic Financial Literacy (MIFL) framework for Islamic schools. We develop a Hypothetical Learning Trajectory (HLT) for fostering students' numeracy and Islamic Financial Literacy (IFL) skills by using MIFL framework that involves various Islamic financial problems as context in mathematics tasks. We chose design research as the method for accomplishing our objective. However, we will discuss about task design and a portion of one of the three major phases of design research, namely pilot experiments. We involved three experts to provide suggestions to improve the tasks and six students from an Islamic junior high school participated in this study. We designed three stages of learning activities. Identifying of math-based Islamic financial information, analyzing math-based Islamic financial context, and applying math-based Islamic financial knowledge and understanding for completing the tasks are the three activities. Results indicate that HLT can indeed assist students in acquiring fundamental arithmetic abilities and advance their IFL. To improve the learning trajectory, we added several sub-sections of activities that bridged the understanding of mathematics and IFL.